2022
DOI: 10.3390/antiox11112105
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein F Knockout Caused Glucose Metabolism Disorder in Young Mice by Disrupting Redox Homeostasis

Abstract: Selenoprotein F (SELENOF) might play an important role in maintaining human health since an increasing number of studies have linked SELENOF deficiency to various pathologies such as cancer and neurodegeneration. We have previously reported on glucose metabolism disorders in SELENOF knockout mice, which imply a novel biological function of SELENOF in glucose metabolism. However, the underlying mechanism and whether the effect of SELENOF on glucose metabolism is age-dependent remain unknown. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Overall, these data indicate that the loss of Selenof exacerbates the metabolic syndrome when animals are exposed to a high fat diet. In contrast, a more recent examination showed that glucose metabolism differences are significant in younger SELENOF KO mice (12 weeks old) via the disruption of redox homeostasis; however, these differences tended to dissipate with age (16 weeks and older) [ 54 ]. Metabolic dysregulation also occurs when diets with excess selenium are consumed by mice and rats [ 55 , 56 ].…”
Section: Selenof’s Putative Roles In Redox Protein Quality Control An...mentioning
confidence: 99%
“…Overall, these data indicate that the loss of Selenof exacerbates the metabolic syndrome when animals are exposed to a high fat diet. In contrast, a more recent examination showed that glucose metabolism differences are significant in younger SELENOF KO mice (12 weeks old) via the disruption of redox homeostasis; however, these differences tended to dissipate with age (16 weeks and older) [ 54 ]. Metabolic dysregulation also occurs when diets with excess selenium are consumed by mice and rats [ 55 , 56 ].…”
Section: Selenof’s Putative Roles In Redox Protein Quality Control An...mentioning
confidence: 99%
“…Given SELENOF's cellular localization within the EnR and its redox activity, it is postulated to play a putative role in disulfide-bond formation and protein redox quality control [10,11]. More recently, depletion of SELENOF in cultured human cells or in Selenof knockout animal models was shown to result in differential expression of metabolism-related genes and associated phenotypes [12][13][14][15][16][17]. In this study, SELENOF-driven functions and phenotypes were examined in normal breast epithelial and breast cancer cells to better understand the role of SELENOF in breast cancer and to identify potential new therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%